Aplicativo Android Para Facilitar à Participação Esportiva de Indivíduos Em Comunidades de Esportes - Souza, Pedro Jemeson Menezes de (Brasil, 2022)
Facilitating access to places that encourage the practice of sports is contributing to the health of the world's population. This work shows a way to connect individuals with sport. To reach a solution, a methodological procedure of bibliographic research was carried out in the literature, the solution was based on personas and scenarios. We built It on the incremental model, using UML diagrams, as well as its implementation and programming approach with Kotlin and SQLite. Thus, we created an android application with the purpose of facilitating the search for places according to the user's preferred sport. The SportGo application allows users to interact with new communities and gain experience in a real environment, It also shows the entire route through Google Maps. As a result, a quantitative research was carried out through questionnaires using the TAM model with the indicators of Perceived Usefulness, Perceived Ease of Use and Usefulness of Use, and had a descriptive analysis of 41 responses. The application has profound implications for future studies and the effectiveness of such an approach is confirmed by empirical data.